Systematic Literature Review:The Effect of The Teams Games Tournament (TGT) Type Cooperative Model on Students' Mathematical Communication Abilities And Learning Independence - Rofiah, Anisa; Nuryadi, Nuryadi (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
Mathematical communication skills and learning independence are very important for students to master. TGT is one of the learning models that can be used to improve mathematical communication and learning independence. This study aims to systematically examine the effect of the Teams Games Tournament (TGT) cooperative learning model on students' mathematical communication skills and learning independence. The method used is the Systematic Literature Review (SLR) with reference to the Kitchenham approach, including the stages of formulating research questions, searching for literature through academic databases (Google Scholar, Garuda, ScienceDirect, ResearchGate), and data analysis and synthesis. The selection was carried out on articles published in 2013–2025 with a focus on the TGT model in the context of mathematics learning and mathematical communication variables and learning independence. From the 15 selected articles, it was found that the TGT model consistently had a positive impact on students' mathematical communication skills. Through collaboration in teams and fun competitive activities, TGT encourages students to actively discuss, convey ideas verbally and in writing, and improve their mastery of mathematical representation. In addition, TGT also plays a role in fostering learning independence by increasing individual responsibility in completing tasks and taking learning initiatives. However, several studies have shown that the relationship between TGT and learning independence is contextual and influenced by internal student factors and learning design. The results of this SLR conclude that TGT is an effective learning strategy that is able to improve two essential competencies of the 21st century, namely mathematical communication and learning independence. Therefore, the implementation of this model is highly recommended as an innovative approach in mathematics learning